Levetiracetam Improves Upper Limb Spasticity in a Patient With Unresponsive Wakefulness Syndrome: A Case Report - Pingue, Valeria; Gentili, Marta; Losurdo, Anna; Clementi, Emilio; Nardone, Antonio (Frontiers in Neuroscience, 2020)
Severe spasticity is a frequent and disabling complication in patients presenting disorders of consciousness that hinders their rehabilitative process, and is strongly correlated with pain reducing patients’ quality of life. Here we present the case of a 52-year-old man in an unresponsive wakefulness syndrome following a hypoxic–ischemic encephalopathy who showed improvement of spasticity following intake of levetiracetam.